Bright and Efficient Pure Red Perovskite Nanocrystals Light‐Emitting Devices via In Situ Modification. (10th November 2021) - Shen, Xinyu; Zhang, Xiaoyu; Wang, Zhenyu; Gao, Xupeng; Wang, Yu; Lu, Po; Bai, Xue; Hu, Junhua; Shi, Zhifeng; Yu, William W.; Zhang, Yu
Abstract: Although light‐emitting devices (LEDs) based on metal halide perovskite nanocrystals (PNCs) developed rapidly in recent years, the luminance of pure red LEDs with the Rec. 2020 standard Commission Internationale de l'Eclairage 1931 color coordinates of (0.708, 0.292) cannot meet the requirement of outdoor display. Herein, a facile in situ modification strategy is proposed to prepare the efficiently luminescent CsPb(Br/I)3 PNCs, where metal bromides are used to create a halide‐rich environment and inhibit the formation of nonradiative surface defects. Synchronously, appropriately increased surface ligands improved the effective exciton confinement. Hence, the modified CsPb(Br/I)3 PNCs exhibited a high photoluminescence quantum yield of 92.0%. Additionally, the electrical conductivity is improved due to the increased hole mobility, and the Auger process is inhibited caused by balanced carrier mobilities. Consequently, LEDs based on the modified CsPb(Br/I)3 PNCs exhibited a maximum luminance of 11233 cd m −2 with the pure red color coordinate (0.704, 0.292) and a peak external quantum efficiency value of 13.2%. Furthermore, the luminance reached 5198 cd m −2 under the driving voltage of 4.4 V. This is the first study to realize a pure red PNC LED with high luminance under low bias, which can meet the requirement of outdoor display. Abstract : In situ metal halide modification strategy is proposed to prepare CsPb(Br/I)3 perovskite nanocrystals (PNCs) with a photoluminescence quantum yield (PLQY) of 92.0% due to the decreased nonradiative recombination rates and increased radiative recombination rates. The luminance reached 11233 cd m −2 for pure red PNC light‐emitting devices with a Commission Internationale de l'Eclairage 1931 color coordinate (0.704, 0.292) due to improved PLQY and balanced carrier injection.